2021
DOI: 10.1136/neurintsurg-2020-017205
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular thrombectomy time metrics in the era of COVID-19: observations from the Society of Vascular and Interventional Neurology Multicenter Collaboration

Abstract: BackgroundUnprecedented workflow shifts during the coronavirus disease 2019 (COVID-19) pandemic have contributed to delays in acute care delivery, but whether it adversely affected endovascular thrombectomy metrics in acute large vessel occlusion (LVO) is unknown.MethodsWe performed a retrospective review of observational data from 14 comprehensive stroke centers in nine US states with acute LVO. EVT metrics were compared between March to July 2019 against March to July 2020 (primary analysis), and between sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“… 2 This observation has since been validated in a larger multicenter study which showed a 28% decline in discharges to IRFs, 3 and a 40% decline in IRF discharges among patients with severe strokes who underwent thrombectomy. 4 The decline in discharge rates to IRFs remains unexplained, and may be the consequence of many patient-level and system-wide factors which warrant further exploration. The implications of a 30-50% loss in rehab-eligible patients receiving aggressive physical, speech, and occupational therapy are tremendous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 This observation has since been validated in a larger multicenter study which showed a 28% decline in discharges to IRFs, 3 and a 40% decline in IRF discharges among patients with severe strokes who underwent thrombectomy. 4 The decline in discharge rates to IRFs remains unexplained, and may be the consequence of many patient-level and system-wide factors which warrant further exploration. The implications of a 30-50% loss in rehab-eligible patients receiving aggressive physical, speech, and occupational therapy are tremendous.…”
Section: Introductionmentioning
confidence: 99%
“…This difference in disability among patients admitted during the COVID-19 period persisted at 3 months (p=0.009).LOS was no different between the study periods (p=0.72; Table2). Between the study periods, there was also no difference in median LOS among patients discharged to IRF (6d [IQR[3][4][5][6][7][8][9][10][11][12] vs. 5d[3][4][5][6][7][8], p=0.54) or to home (2d [IQR 1-4] vs. 2d [IQR 1-4], p=0.92), although LOS was generally longer among patients discharged to IRF versus home (6d [IQR 3-9] vs. 2d [IQR 1-4], p<0.001). Of the 11 patients with COVID-19 and stroke, 4 were discharged to IRF, 3 to a subacute inpatient rehabilitation facility, and 3 went home.…”
mentioning
confidence: 99%
“…Across studies, these were widely attributed to precautions associated with COVID-19 such as symptom screening, additional PPE requirements, and isolation policies within hospitals (figure 3A). Minimal delays to stroke treatment during COVID-19 have also been identified in large multicenter studies,14 further showing the ability of hospital systems to adapt workflow to maximize patient outcomes. Interestingly, our analysis showed only a 2.8% increase in mean DTG times, but a 19.7% increase in mean DTR times.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, there was a controversy among different reports regarding the change of pattern of acute stroke management [ 10 ] that resulted in either an increased, decreased, or no change of onset to door or door to needle times [ 11 ]. Consequently, the outcome of stroke has changed to variable degrees in different health facilities [ 4 ].…”
Section: Introductionmentioning
confidence: 99%